2013
DOI: 10.1109/tns.2013.2256148
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 2-Directional Magnetic Biasing Used for Tuning of a Ferrite-Loaded Re-entrant Cavity

Abstract: SummaryCavities that are partially filled with ferrite material provide a tunable resonance frequency by making use of the changing µ-characteristics of ferrites when exposed to an external magnetic bias field. The concept of using either parallel or perpendicular magnetic biasing to reach a certain resonance frequency of a cavity has been known for many years. However, a cavity based on superposition of perpendicular and parallel magnetic fields to obtain improved ferrite characteristics was suggested in W. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…Yet, the quality factor strongly depends on both field components. Consequently, this model is compliant with the experimental finding that a 2-directional bias scheme is beneficial [39]. The results for the resonance frequency and quality factor are summarized in figure 4.9.…”
Section: Analysis Of Higher-order Modessupporting
confidence: 80%
See 2 more Smart Citations
“…Yet, the quality factor strongly depends on both field components. Consequently, this model is compliant with the experimental finding that a 2-directional bias scheme is beneficial [39]. The results for the resonance frequency and quality factor are summarized in figure 4.9.…”
Section: Analysis Of Higher-order Modessupporting
confidence: 80%
“…As expected from theory [102], such bias schemes might lead to a higher quality factor while sustaining the same tuning range. This fact has been successfully confirmed in recent experiments [39]. A numerical analysis of a 2-directional bias scheme requires the knowledge of all components of the permeability tensor (2.22) for all magnetization states.…”
Section: -Directional Bias Schemementioning
confidence: 55%
See 1 more Smart Citation
“…Miniaturization can also be achieved by increasing the other parameter μ r (such as by using ferrite based materials). But, reports suggests that bulk ferrites generally have high saturation magnetization and dispersive magnetic losses [4][5][6] and needs strong external dc-bias fields to alter its permeability property [7], making it unsuitable for compact applications requiring higher efficiency. Further, shift of operational frequency of resonant devices on ferrite substrates due to application of external bias [8,9] causes difficulty in integrating it with other systems.…”
Section: Introductionmentioning
confidence: 99%
“…The garnet G-510 from Trans-Tech, Inc. [7] was evaluated to be most suitable for perpendicular biasing within a frequency range of 18 to 40 MHz with regards to the available range in relative permeability and related magnetic losses. In [8] and [9] a possible resonance sweep was investigated by using G-510 toroidal samples in a re-entrant measurement cavity. It was shown that superposition of a magnetic bias with both perpendicular and parallel components with respect to the RF magnetic field can be advantageous in terms of frequency tuning range and quality factor.…”
Section: Introductionmentioning
confidence: 99%